Sympathectomy for Palmar Hyperhidrosis - Tulay, Cumhur Murat (Indian J Surg, 2013)
Palmar hyperhidrosis is an important situation that may cause emotional and work-related problems. Although local treatment and psychotherapy have been used for palmar hyperhidrosis, the choice of treatment for palmar hyperhidrosis is video-assisted thoracoscopic sympathectomy. Retrospective analysis of 120 bilateral thoracoscopic sympathectomies (60 patients) was done in this study. Earlier, 12 of 60 patients (20 %) had been operated on by other surgeons who used clipping method for palmar hyperhidrosis in different hospitals within 1 year. The procedure was performed under general anesthesia using single-lumen endotracheal tube. Sympathetic chain resection was performed between lower level of the second rib and upper level of the fourth rib. Intercostal blockage at three levels was performed, while thoracoscopic control of the injection sites was done. We observed improvement of symptoms in 95 %, mild compensatory sweating in 20 %, and excessive dryness of hands in 10 % in our patients.